Preliminary Investigation of Catechin as a Natural Complexing Agent for Selective Recovery of Tantalum and Niobium from Hydrometallurgical Leachate of Bangka Tin Slag 2 - Sulaksana Permana; Agustino Zulys; Widiantari Nofriandani; Kurnia Trinopiawan; Riesna Prassanti; Iwan Susanto; Asep Mohamad Noor; Johny Wahyuadi M. Soedarsono (EKSPLORIUM, 2026)
Bangka Tin Slag 2 (BTS 2), a byproduct of tin processing, contains strategic metals such as tantalum (Ta) and niobium (Nb) in oxide forms. This study explores the potential of catechin extract from green tea leaves (Camellia sinensis) as a complexing agent for the recovery of Ta2O5 and Nb2O5 from BTS 2 following a staged leaching process. The material underwent a staged leaching process, defined as a sequential alkali-acid treatment (NaOH followed by HCl) to remove major impurities, followed by hydrofluoric acid (HF) digestion. Catechin was isolated with a yield of 4.73%. Leaching optimization revealed that 4 M HF was optimal, achieving extraction efficiencies of 3.879% for Ta and 23.109% for Nb. Interaction studies using Job’s method showed a 1:1 stoichiometric ratio (metal:ligand) for the complexation. However, catechin exhibited a dominant complexing efficiency with iron (Fe3+) at 12.23%, compared to only 1.55% with Ta5+ and 0.21% with Nb5+. Based on the Hard-Soft Acid-Base (HSAB) theory, this preferential binding occurs because Fe3+ acts as a hard acid that matches perfectly with the hard oxygen-donor phenolic groups of catechin, whereas the highly charged Ta5+ and Nb5+ ions form overly stable fluoro-complexes in the leachate that restrict ligand exchange. These findings indicate that while catechin is a potent complexing agent, its selectivity toward Ta and Nb requires further enhancement or an intermediate iron-removal step.